2022
DOI: 10.3892/mco.2022.2492
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PD‑L1 and CD4+ tumor‑infiltrating lymphocytes predict survival in head and neck squamous cell carcinoma

Abstract: The clinical efficacy of immune checkpoint blockade has been recently demonstrated in a variety of cancer types. The aim of the present study was to characterize the expression profile of tumor-infiltrating lymphocytes (TILs) and programmed death-ligand 1 (PD-L1) in head and neck squamous carcinoma (HNSCC). A total of 63 patients with HNSCC were enrolled in the present study. CD3 + and CD4 + TILs and the expression of PD-L1 were detected by immunohistochemistry. PD-L1 mRNA levels were evaluated by reverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…A total of 3825 publications were identified, and of 82 eligible articles, 17 studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] met inclusion criteria and hence were considered eligible for our meta-analysis (Figure 1). Characteristics of these studies conducted in a total of 3190 patients with HNSCC at various sites (including the oral cavity,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 3825 publications were identified, and of 82 eligible articles, 17 studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] met inclusion criteria and hence were considered eligible for our meta-analysis (Figure 1). Characteristics of these studies conducted in a total of 3190 patients with HNSCC at various sites (including the oral cavity,…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3825 publications were identified, and of 82 eligible articles, 17 studies 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 met inclusion criteria and hence were considered eligible for our meta-analysis ( Figure 1 ). Characteristics of these studies conducted in a total of 3190 patients with HNSCC at various sites (including the oral cavity, oropharynx, larynx, and hypopharynx) with stage I through IV disease who underwent radical curative treatment are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the TILs, CD3, CD8 (effector/cytotoxic), and CD4 (helper) T cells are recognized to have an anti-tumor immune response and found to positively correlate with SCC patients’ favorable outcomes. One report showed that among 63 patients with HNSCC, all of the tumors have TILs positive for CD3 and CD4 immunohistochemistry, and increased CD4-positive cell infiltration was associated with improved survival compared with the poor CD4-positive cell-infiltrating tumors [ 111 ]. In another report, 50 patients with OSCC were assessed for CD8- and CD4-positive cells and they found that CD8-positive cells were more abundant than CD4 in tumor specimens and there is a negative correlation between CD8 infiltration and metastasis [ 112 ].…”
Section: Available Treatments For Sccmentioning
confidence: 99%